A Series on Diseases in the Florida Vegetable Garden: TOMATO - Gary Vallad; Ken Pernezny; Tim Momol (EDIS)
Revised! PP200, an 8-page illustrated fact sheet by Gary Vallad, Ken Pernezny, and Tim Momol, describes several diseases most likely to appear on garden tomatoes in Florida, providing information for identification and management of each. Published by the UF Department of Plant Pathology, February 2009.